IS THE EDUCATIONAL SYSTEM WEAKENING? A COMPARATIVE STUDY OF PROFICIENCY TESTS - LAKEHAL–AYAT, Karima (Journal of Human Sciences, 2008)
The paper reports on a comparative study of two populations of students in a proficiency test; the first population concerns a sample of first year students we tested in 1996 for first year students enrolled in the English department in 2005, and tested in 2006. Both populations received the same treatment: a our Magister thesis; the second concerns sociological questionnaire, and three tests aiming at evaluating their competence in English. The sociological questionnaire showed that the student body has changed in the intervening time. The results of the tests proved to be enlightening in the fact that the 2006 test-takers performed less well than their 1996 counterparts, particularly in the Cloze test.